Analisis Pengaruh Filsafat Post Modern Terhadap Pendidikan - Arif Fiandi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this research is to determine and analyze the influence of Post Modern philosophy on education. This research method uses literature review by examining various relevant literature sources. The development of science cannot be separated from the development of philosophy. Philosophy as the mother of science has given birth to various fields of scientific discipline. The development of philosophy started from classical philosophy to post-modern philosophy which was very sharp in criticizing previous phases of philosophy. The development of post-modern philosophy has penetrated and influenced the development of various areas of life, including education. Post-modern philosophy provides color to education through various elements, from the curriculum to learning methods and strategies.